Block copolymer composition and adhesive composition

JP7641720B2Active Publication Date: 2025-03-07ASAHI KASEI KOGYO KABUSHIKI KAISHA
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2020171344
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-10-09
Publication Date
2025-03-07
Estimated Expiration
2040-10-09

AI Technical Summary

Benefits of technology

【0009】 本発明によれば、低粘度性と保持力性能とのバランスに優れた粘接着剤組成物、及び当該粘接着剤組成物に用いるブロック共重合体組成物を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007641720000003
    Figure 0007641720000003
  • Figure 0007641720000001
    Figure 0007641720000001
  • Figure 0007641720000002
    Figure 0007641720000002
Patent Text Reader

Abstract

To provide a block copolymer composition that strikes a balance between low viscosity and holding power and is used in an adhesive composition.SOLUTION: A block copolymer composition contains component (a) and component (b), with (a) and (b) being block copolymers. (b) includes component (b-1) with the ratio of its Mw to Mw of (a) being 1.5 or more and less than 2.5, component (b-2) with the ratio of its Mw to Mw of (a) being 2.5 or more and less than 3.4, and component (b-3) with the ratio of its Mw to Mw of (a) being 3.4 or more and less than 4.5. The content of (b-3) is 35 mass% or more relative to the total of (b). The amount of St in (a) and (b) is 22.0-26.0 mass% relative to the total amount of (a) and (b). In (a) and (b), the amount of vinyl bonds V(%) is 25% or more. In (a) and (b), the hydrogenation rate H(%) satisfies formula (1) in relation to the amount of vinyl bonds V(%). In (a) and (b), the hydrogenation rate of vinyl bonds before hydrogenation is 80% or more. Formula (1): V+50>H>V+10.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a block copolymer composition and an adhesive composition. [Background technology]

[0002] In recent years, vinyl aromatic monomer-conjugated diene monomer block copolymers (e.g., SBS: styrene-butadiene-styrene block copolymer, SIS: styrene-isoprene-styrene block copolymer) have been widely used as base polymers for solution-type and hot-melt-type adhesives and pressure-sensitive adhesives. For example, Patent Documents 1 and 2 disclose adhesive compositions or pressure-sensitive adhesive compositions using SBS or SIS.

[0003] However, these adhesive compositions or pressure-sensitive adhesive compositions using SBS or SIS have problems in that they have high melt viscosity and an insufficient balance between solubility, coatability, and pressure-sensitive adhesive properties such as adhesion, etc. As a method for improving these properties, Patent Documents 3 and 4 disclose techniques for producing pressure-sensitive adhesive compositions containing triblock copolymers, diblock copolymers, and further tri- or tetra-branched copolymers thereof. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Special Publication No. 44-17037 [Patent Document 2] Special Publication No. 56-49958 [Patent Document 3] International Publication No. 2015 / 111675 [Patent Document 4] International Publication No. 2015 / 111669 Summary of the Invention [Problem to be solved by the invention]

[0005] However, the pressure-sensitive adhesive compositions and adhesive compositions disclosed in Patent Documents 3 and 4 are still insufficient in terms of the effects of improving the various properties described above. In particular, in applications requiring high holding power, such as tapes, there is a problem in that an improvement in the balance between low viscosity and holding power performance is required.

[0006] In view of the above-mentioned problems in the conventional art, an object of the present invention is to provide a pressure-sensitive adhesive composition having an excellent balance between low viscosity and holding power performance, and a block copolymer composition for use in the pressure-sensitive adhesive composition. [Means for solving the problem]

[0007] Means for Solving the Problems The present inventors have conducted intensive research to solve the above problems, and as a result have found that the above problems can be solved by a block copolymer composition having a specific structure and composition, thereby completing the present invention. That is, the present invention is as follows.

[0008] [1] Component (a) is 50% by mass or more and 70% by mass or less, A block copolymer composition containing 30% by mass or more and 50% by mass or less of component (b). So, The component (a) is a polymer block (A) mainly composed of one vinyl aromatic monomer unit. and at least one polymer block (B) mainly composed of a conjugated diene monomer unit. and a weight average molecular weight of 50,000 or more and 80,000 or less. the law of nature, The component (b) is a polymer block having at least two vinyl aromatic monomer units as a main component. block (A) and at least one polymer block (B) mainly composed of a conjugated diene monomer unit. ) is a block copolymer containing The component (b) is coupled with the component (a) by a coupling agent having four or more functional groups. It is a polymer that has been bonded to the polymer, The ratio of the weight average molecular weight of the component (b) to the weight average molecular weight of the component (a) is 1. a component (b-1) having a weight-average molecular weight ratio of 2.5 or more to less than 2.5 relative to the weight-average molecular weight of the component (a), a component (b-2) having a weight-average molecular weight ratio of 2.5 or more to less than 3.4 relative to the weight-average molecular weight of the component (a), and a component (b-3) having a weight-average molecular weight ratio of 3.4 or more to less than 4.5 relative to the weight-average molecular weight of the component (a), The content of the component (b-3) is 35 mass% or more based on the total content of the component (b), The content of vinyl aromatic monomer units in the components (a) and (b) is 22.0% by mass or more and 26.0% by mass or less, based on the total amount of the components (a) and (b); The vinyl groups of the conjugated diene monomer units contained in the components (a) and (b) before hydrogenation The amount of bond V(%) is 25% or more, The unsaturated double bonds of the conjugated diene monomer units of the components (a) and (b) Hydrogenation rate H (%) is The hydrogenation rate H (%) is 30% or more and 55% or less, In relation to the vinyl bond content V (%), the following formula is satisfied: (1’) Fulfilling The vinyl groups of the conjugated diene monomer units contained in the components (a) and (b) before hydrogenation The hydrogenation rate of the aryl bonds is 80% or more. Block copolymer compositions. V+25>H>V+15...Formula (1') [2] The weight average molecular weight of the polymer block (A) contained in the component (a) is 14.00 The block copolymer composition according to [1] above, wherein the molecular weight is 0 or more and 19,000 or less. [3] The component (a) is a block copolymer represented by (AB) and / or (AB)X. It is a combination, The component (b-1) is (AB)2X, The component (b-2) is (AB)3X, The component (b-3) is a block copolymer represented by (AB)4X, The block copolymer composition according to [1] or [2] above, (A represents a polymer block (A), B represents a polymer block (B), and X represents a coupling (Residues of a blocking agent or a polymerization initiator.) [4] 100 parts by mass of the block copolymer composition according to any one of [1] to [3] above; 1 to 250 parts by mass of a tackifier; 0 to 120 parts by mass of a softener; A pressure-sensitive adhesive composition comprising: Effect of the Invention

[0009] According to the present invention, it is possible to provide a pressure-sensitive adhesive composition having an excellent balance between low viscosity and holding power performance, and a block copolymer composition used in the pressure-sensitive adhesive composition. [Brief description of the drawings]

[0010] [Figure 1] A diagram showing vertical division from the inflection points between the peaks of components (b-1), (b-2), and (b-3) is shown. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] Hereinafter, an embodiment of the present invention (hereinafter, referred to as "the present embodiment") will be described in detail. It should be noted that the following embodiment is merely an example for explaining the present invention, and is not intended to limit the present invention to the following content. The present invention can be implemented in various modifications within the scope of the gist thereof.

[0012] [Block Copolymer Composition] The block copolymer composition of the present embodiment is It contains 50% by mass or more and 70% by mass or less of component (a) and 30% by mass or more and 50% by mass or less of component (b). The component (a) is a block copolymer containing a polymer block (A) mainly made of one vinyl aromatic monomer unit and a polymer block (B) mainly made of at least one conjugated diene monomer unit, and having a weight average molecular weight of 50,000 or more and 80,000 or less. The component (b) is a block copolymer containing at least two polymer blocks (A) mainly composed of vinyl aromatic monomer units and at least one polymer block (B) mainly composed of conjugated diene monomer units. The component (b) is a polymer formed by coupling the component (a) with a coupling agent having tetrafunctional or higher functionality, and the component (b) includes a component (b-1) having a weight-average molecular weight ratio to the weight-average molecular weight of the component (a) of 1.5 or more and less than 2.5, a component (b-2) having a weight-average molecular weight ratio to the weight-average molecular weight of the component (a) of 2.5 or more and less than 3.4, and a component (b-3) having a weight-average molecular weight ratio to the weight-average molecular weight of the component (a) of 3.4 or more and less than 4.5. The content of the component (b-3) is 35 mass % or more based on the total amount of the component (b). The content of the vinyl aromatic monomer unit in the component (a) and the component (b) is 22.0% by mass or more and 26.0% by mass or less based on the total amount of the component (a) and the component (b). The conjugated diene monomer units contained in the components (a) and (b) each have a vinyl bond content V (%) of 25% or more before hydrogenation. The hydrogenation rate H (%) of the unsaturated double bonds of the conjugated diene monomer units contained in the components (a) and (b) satisfies the following formula (1) in relation to the vinyl bond amount V (%), and the hydrogenation rate of the vinyl bonds of the conjugated diene monomer units contained in the components (a) and (b) before hydrogenation is 80% or more. V+50>H>V+10...Formula (1)

[0013] When the block copolymer composition of the present embodiment has the above-mentioned configuration, a pressure-sensitive adhesive composition having an excellent balance between low viscosity and holding power performance can be obtained.

[0014] The term "vinyl aromatic monomer unit" refers to a structure resulting from polymerization of one vinyl aromatic hydrocarbon compound, and the term "conjugated diene monomer unit" refers to a structure resulting from polymerization of one conjugated diene compound.

[0015] The "polymer block (A) mainly composed of vinyl aromatic monomer units" means a polymer block containing 80 mass % or more, preferably 85 mass % or more, and more preferably 95 mass % or more of vinyl aromatic monomer units. Further, the term "polymer block (B) mainly composed of conjugated diene monomer units" means a polymer block containing more than 70% by mass, preferably 85% by mass or more, and more preferably 95% by mass or more of conjugated diene monomer units. Each component will be described in more detail below.

[0016] (Component (a)) <Weight average molecular weight> Component (a) is a block copolymer having a weight average molecular weight of 50,000 or more and 80,000 or less, which comprises a polymer block (A) mainly composed of one vinyl aromatic monomer unit and a polymer block (B) mainly composed of at least one conjugated diene monomer unit. The lower limit of the weight average molecular weight of component (a) is 50,000 or more, preferably 60,000 or more, and more preferably 65,000 or more. When the weight average molecular weight of component (a) is in the above range, the retention power tends to be improved. In addition, the upper limit of the weight average molecular weight of component (a) is 80,000 or less, preferably 78,000 or less, and more preferably 76,000 or less. When the weight average molecular weight of component (a) is in the above range, the low viscosity tends to be improved. The weight average molecular weight of the component (a) can be determined by the evaluation method described in the Examples. The weight average molecular weight of the component (a) can be controlled within the above numerical range by adjusting the polymerization conditions, such as the amount of monomer added in the polymerization step, the polymerization time, and the polymerization temperature.

[0017] <Structure of component (a)> The structure of component (a) is not particularly limited, but is preferably one or more of the structures represented by the following formulae (A1), (A2), (A11) and (A21). In particular, when component (a) has a structure such as (A1) or (A2), a block copolymer composition and a pressure-sensitive adhesive composition having excellent holding power tend to be obtained. AB···(A1) (AB)X···(A2) BAB···(A11) (BAB)X···(A21) In the above formula, A represents a polymer block mainly composed of vinyl aromatic monomer units, B represents a polymer block mainly composed of conjugated diene monomer units, and X represents a residue of a coupling agent or a residue of a polymerization initiator.

[0018] <Content of vinyl aromatic monomer units in component (a)> The content of vinyl aromatic monomer units in component (a) is 22.0% by mass or more and 26.0% by mass or less. The lower limit of the content of vinyl aromatic monomer units in component (a) is 22.0% by mass or more, preferably 22.5% by mass or more, and more preferably 23.0% by mass or more. When the content of the vinyl aromatic monomer unit in component (a) is within the above range, the holding power tends to be improved. The upper limit of the content of the vinyl aromatic monomer unit in component (a) is 26.0 mass% or less, preferably 25.5 mass% or less, and more preferably 25.0 mass% or less. When the content of the vinyl aromatic monomer unit in component (a) is within the above range, the low viscosity tends to be improved, particularly in the low temperature range (about 160°C or less).

[0019] <Amount of vinyl bonds in the conjugated diene monomer unit of component (a) before hydrogenation> The amount of vinyl bonds (V) of the conjugated diene monomer units contained in component (a) before hydrogenation is 25% or more, the hydrogenation rate of the vinyl bonds of the conjugated diene monomer units contained in component (a) before hydrogenation is 80% or more, and the hydrogenation rate (H) of the unsaturated double bonds of the conjugated diene monomer units contained in component (a) satisfies the following formula (1). V+50>H>V+10...Formula (1)

[0020] <Hydrogenation rate of vinyl bonds before hydrogenation of conjugated diene monomer units of component (a)> The hydrogenation rate of vinyl bonds in the conjugated diene monomer units contained in component (a) before hydrogenation is 80% or more, preferably 85% or more, and more preferably 90% or more. When the hydrogenation rate of the vinyl bond of the conjugated diene monomer unit contained in component (a) before hydrogenation is within the above range, weather resistance and heat resistance tend to be improved.

[0021] <Hydrogenation rate of unsaturated double bonds in conjugated diene monomer units of component (a)> Furthermore, when the hydrogenation rate H of the unsaturated double bonds of the conjugated diene monomer units contained in the component (a) satisfies the above (formula 1), the component (a) exhibits high weather resistance and heat resistance. From the viewpoint of improving the compatibility with a tackifier resin generally used in pressure-sensitive adhesive compositions and enhancing the pressure-sensitive adhesive performance, the hydrogenation rate (H) of the unsaturated double bonds of the conjugated diene monomer units contained in component (a) is preferably 30% or more and 70% or less, more preferably 40% or more and 60% or less, and even more preferably 45% or more and 55% or less.

[0022] <Amount of vinyl bonds (V) of the conjugated diene monomer unit of component (a) before hydrogenation> The vinyl bond content (V) of the conjugated diene monomer unit of the component (a) before hydrogenation is 25% or more, preferably 28% or more, and more preferably 28% or more. It is preferably 30% or more. When the vinyl bond amount (V) of the conjugated diene monomer unit contained in the component (a) before hydrogenation is within the above range, low viscosity tends to be improved. From the viewpoint of improving low viscosity, it is preferable that the hydrogenation rate (H) of the unsaturated double bonds of the conjugated diene monomer units contained in the component (a) satisfies the following (formula 2). V+25>H...(Formula 2)

[0023] The vinyl bond amount of the conjugated diene monomer unit in the component (a) constituting the block copolymer composition and the component (b) described below can be controlled by using, for example, ethers, tertiary amines, etc. Specifically, one or a mixture of two or more selected from ethylene glycol dimethyl ether, tetrahydrofuran, α-methoxytetrahydrofuran, N,N,N',N'-tetramethylethylenediamine, etc. is used. These are preferably added to the polymerization solvent at a stage before adding the conjugated diene monomer.

[0024] <Weight average molecular weight of polymer block (A) contained in component (a)> The weight average molecular weight of the polymer block (A) contained in the component (a) is preferably at least 14,000, more preferably at least 15,000, and even more preferably at least 16,000. When the weight average molecular weight of the polymer block (A) contained in the component (a) is within the above range, the retention power tends to be improved. Furthermore, the weight average molecular weight of the polymer block (A) contained in the component (a) is preferably not more than 19,000, and more preferably not more than 18,000. When the weight average molecular weight of the polymer block (A) contained in the component (a) is within the above range, low viscosity tends to be improved. The weight average molecular weight of the polymer block (A) contained in the component (a) can be measured by the method described in the Examples below. The weight average molecular weight of the polymer block (A) contained in component (a) can be controlled within the above numerical range by adjusting the type and amount of monomer added in the polymerization step of component (a) in the production process of the block copolymer composition.

[0025] The content of the vinyl aromatic monomer unit in the block copolymer constituting the block copolymer composition of the present embodiment, the amount of vinyl bonds V of the conjugated diene monomer units before hydrogenation, the hydrogenation rate of the vinyl bonds of the conjugated diene monomer units before hydrogenation, the hydrogenation rate H of the unsaturated double bonds of the conjugated diene monomer units, and the weight average molecular weight of the polymer block (A) can be measured according to the method for measuring the physical properties of the block copolymer composition described in the Examples below.

[0026] (ingredient (b)) Component (b) is a block copolymer containing at least two polymer blocks (A) mainly composed of vinyl aromatic monomer units and at least one polymer block (B) mainly composed of conjugated diene monomer units. Component (b) is a polymer obtained by coupling component (a) with a tetrafunctional or higher coupling agent. In addition, component (b) contains component (b-1) having a weight average molecular weight ratio of 1.5 or more and less than 2.5 to the weight average molecular weight of component (a), component (b-2) having a weight average molecular weight ratio of 2.5 or more and less than 3.4 to the weight average molecular weight of component (a), and component (b-3) having a weight average molecular weight ratio of 3.4 or more and less than 4.5 to the weight average molecular weight of component (a). The content of the component (b-3) is 35 mass % or more based on the total amount of the component (b). When component (b) has the above structure, the resulting block copolymer composition has an excellent balance between retention power and low viscosity. The content of the component (b-3) is 35% by mass or more, preferably 40% by mass or more, and more preferably 45% by mass or more, based on the total amount of the component (b). The content of the component (b-3) in the above range tends to improve the retention. The content of the component (b-3) is preferably 65% ​​by mass or less, more preferably 60% by mass or less, and even more preferably 55% by mass or less, based on the total amount of the component (b). The content of the component (b-3) in the above range tends to improve the low viscosity. From the viewpoint of improving the retention power, the content of component (b-3) is preferably greater than the content of component (b-2), and the content of component (b-2) is preferably greater than the content of component (b-1).

[0027] Incidentally, whether the component (b-1), the component (b-2), and the component (b-3) are contained as the component (b) in the block copolymer composition of the present embodiment can be determined based on the difference in the peak position of the molecular weight distribution curve of gel permeation chromatography (hereinafter also referred to as "GPC") under the following specific conditions. That is, by confirming in a GPC chart a peak at 1.5 to less than 2.5 times the weight average molecular weight of component (a) (component (b-1)), a peak at 2.5 to less than 3.4 times the weight average molecular weight of component (a) (component (b-2)), and a peak at 3.4 to less than 4.5 times the weight average molecular weight of component (a) (component (b-3)), it is possible to confirm components (b-1), (b-2), and (b-3) contained in the block copolymer composition. The weight average molecular weight of the component (b) can be determined by the evaluation method described in the Examples.

[0028] The area ratios of components (b-1), (b-2), and (b-3) to the total area of ​​component (b) can be determined by performing GPC measurement using the apparatus (ACQUITY APC system) and conditions described in the Examples below, followed by vertical division up to the baseline at the inflection points between the peaks of the GPC curve using the system software also described in the Examples. Here, the inflection point between the peaks of each of the components (b-1), (b-2), and (b-3) is the lowest point (valley peak) between adjacent peaks in the vertical direction. If the lowest points are consecutive, the midpoint is taken as the inflection point. Using the inflection points, vertical division is performed using a predetermined waveform separation software, and after division, the weight average molecular weight and area ratio of each component are calculated. The contents of the components (b-1) to (b-3) can be calculated from the area ratio. FIG. 1 shows a diagram in which the inflection points between the peaks of components (b-1), (b-2), and (b-3) were determined and vertically divided.

[0029] The structure of component (b) is not particularly limited, but the component (b-1) is preferably a structure represented by one or more of the following formulae (B1) and (B11), the component (b-2) is preferably a structure represented by one or more of the following formulae (B2) and (B21), and the component (b-3) is preferably a structure represented by one or more of the following formulae (B3) and (B31). From the viewpoint of improving the retention power, it is particularly preferable that the component (b-1) has a structure represented by the following formula (B1), the component (b-2) has a structure represented by the following formula (B2), and the component (b-3) has a structure represented by the following formula (B3). (AB)2X···(B1) (BAB)2X···(B11) (AB)3X···(B2) (BAB)3X···(B21) (AB)4X···(B3) (BAB)4X···(B31)

[0030] In the above formulas, A represents a polymer block mainly composed of a vinyl aromatic monomer unit, B represents a polymer block mainly composed of a conjugated diene monomer, and X represents a residue of a coupling agent or a residue of a polymerization initiator.

[0031] Since component (b) is a coupling product of the above-mentioned component (a), the content of vinyl aromatic monomer units in component (b), the amount of vinyl bonds (V) before hydrogenation of the conjugated diene monomer units contained in component (b), the hydrogenation rate of vinyl bonds before hydrogenation of the conjugated diene monomer units contained in component (b), the hydrogenation rate (H) of unsaturated double bonds of the conjugated diene monomer units contained in component (b), and the range of the weight-average molecular weight of the polymer block (A) contained in component (b) are in the same numerical ranges as those of component (a) for the same reasons as those described in the section for component (a) above.

[0032] The block copolymer composition of the present embodiment contains components (a) and (b) as essential constituents, and therefore the content of vinyl aromatic monomer units in components (a) and (b) is 22.0% by mass or more and 26.0% by mass or less, the vinyl bond amount V (%) of the conjugated diene monomer units contained in the components (a) and (b) before hydrogenation is 25% or more, the hydrogenation rate H (%) of the unsaturated double bonds of the conjugated diene monomer units contained in the components (a) and (b) satisfies the following formula (1) in relation to the vinyl bond amount V (%), and the hydrogenation rate of the vinyl bonds of the conjugated diene monomer units contained in the components (a) and (b) before hydrogenation is 80% or more. V+50>H>V+10...Formula (1) That is, these physical properties are in the same numerical ranges as those of component (a) for the same reasons as those described above in the section on component (a).

[0033] (Block copolymer composition containing component (a) and component (b)) The block copolymer composition of the present embodiment contains 50% by mass or more and 70% by mass or less of component (a) and 30% by mass or more and 50% by mass or less of component (b). Since component (a) has a lower molecular weight than component (b), a high content of component (a) improves low viscosity. From these viewpoints, the content of component (a) is preferably 53% by mass or more, and more preferably 55% by mass or more. If the content of component (a) is too high, crosslinking is not sufficiently formed and the holding power tends to decrease, so the content of component (a) is preferably 67% by mass or less, and more preferably 65% ​​by mass or less. When the content of component (b-3), which exerts high holding power, is high in component (b), a block copolymer composition and a pressure-sensitive adhesive composition having high holding power tend to be obtained. Therefore, the content of component (b) is preferably 33% by mass or more, more preferably 35% by mass or more. Since component (b) has a higher molecular weight than component (a), if the content of component (b) is too high, the low viscosity property decreases. Therefore, the content of component (b) is preferably 47% by mass or less, and more preferably 45% by mass or less.

[0034] Examples of the vinyl aromatic hydrocarbon compound in the vinyl aromatic hydrocarbon compound unit constituting the polymer blocks in component (a) and component (b) include, but are not limited to, alkylstyrenes such as styrene, α-methylstyrene, p-methylstyrene, and p-tert-butylstyrene; alkoxystyrenes such as p-methoxystyrene; vinylnaphthalene, and the like. Of these, styrene is preferred as the vinyl aromatic hydrocarbon. The vinyl aromatic hydrocarbon compounds may be used alone or in combination of two or more. The conjugated diene compound in the conjugated diene monomer units constituting the polymer blocks in components (a) and (b) is not particularly limited as long as it is a diolefin having a conjugated double bond, and examples thereof include 1,3-butadiene, 2-methyl-1,3-butadiene (isoprene), 2,3-dimethyl-1,3-butadiene, 1,3-pentadiene, and 1,3-hexadiene. Among these, 1,3-butadiene and isoprene are preferred as the conjugated diene compound. Furthermore, the use of 1,3-butadiene is more preferred because it tends to result in a pressure-sensitive adhesive composition having excellent heat aging resistance and light resistance. The conjugated diene compounds may be used alone or in combination of two or more kinds.

[0035] [Method for producing block copolymer composition] (Polymerization and Coupling Reactions) An example of a method for producing the block copolymer composition of the present embodiment includes a polymerization step of copolymerizing a vinyl aromatic hydrocarbon compound such as styrene and a conjugated diene compound such as butadiene in an inert hydrocarbon solvent using an organolithium compound as a polymerization initiator to obtain a block copolymer, and a coupling step of reacting the obtained block copolymer with a coupling agent to obtain component (a) and component (b). In this case, the coupled block copolymer becomes component (b), and the remaining uncoupled block copolymer becomes component (a). In addition, by controlling the amount of coupling agent added in this coupling reaction, the contents of components (a) and (b) can be adjusted to fall within the above-mentioned predetermined ranges. The weight average molecular weight of components (a) and (b) can be adjusted by controlling the amount of a polymerization initiator such as an organolithium compound. After the polymerization reaction is completed, a coupling reaction is carried out, and water, an alcohol, an acid, or the like is added to deactivate the active species. Thereafter, the polymerization solvent is separated, for example, by steam stripping, and then the mixture is dried to obtain components (a) and (b).

[0036] The polymerization method for the block copolymer of component (a) and component (b) is not particularly limited, but examples thereof include polymerization methods such as coordination polymerization, anionic polymerization, and cationic polymerization. Among these, anionic polymerization is preferred from the viewpoint of easy control of structure.As the method for producing block copolymer by anionic polymerization, known methods can be used, and are not particularly limited, but for example, the methods described in JP-B-36-19286, JP-B-43-17979, JP-B-46-32415, JP-B-49-36975, JP-B-48-2423, JP-B-48-4106, JP-B-56-28925, JP-A-59-166518, JP-A-60-186577 etc. can be mentioned.

[0037] The inert hydrocarbon solvent used in the polymerization step of components (a) and (b) is not particularly limited, but examples thereof include aliphatic hydrocarbons such as butane, pentane, hexane, isopentane, heptane, octane, isooctane, etc., alicyclic hydrocarbons such as cyclopentane, methylcyclopentane, cyclohexane, methylcyclohexane, ethylcyclohexane, etc., aromatic hydrocarbons such as benzene, toluene, ethylbenzene, xylene, etc. These may be used alone or in combination of two or more.

[0038] In addition, the organolithium compound used as a polymerization initiator in the polymerization step of components (a) and (b) is not particularly limited, and known compounds can be used, such as ethyl lithium, propyl lithium, n-butyl lithium, sec-butyl lithium, tert-butyl lithium, phenyl lithium, propenyl lithium, and hexyl lithium. In particular, n-butyl lithium and sec-butyl lithium are preferred. The organolithium compound may be used alone or in a mixture of two or more kinds.

[0039] As the coupling agent for obtaining the multi-branched block copolymer, known coupling agents can be used. Examples of tetrafunctional coupling agents include, but are not limited to, tetrafunctional halogenated alkanes such as carbon tetrachloride, carbon tetrabromide, and tetrachloroethane; tetrafunctional halogenated silanes such as tetrachlorosilane and tetrabromosilane; tetrafunctional alkoxysilanes such as tetramethoxysilane and tetraethoxysilane; and tetrafunctional tin compounds such as tetrachlorotin, tetrabromotin, and tetrabutyltin. The pentafunctional or higher coupling agent is not particularly limited, but examples thereof include 1,1,1,2,2-pentachloroethane, perchloroethane, pentachlorobenzene, perchlorobenzene, octabromodiphenyl ether, decabromodiphenyl ether, etc. In addition, epoxidized soybean oil, difunctional to hexafunctional epoxy group-containing compounds, carboxylic acid esters, polyvinyl compounds such as divinylbenzene, etc. may also be used. The coupling agent may be used alone or in combination of two or more kinds. Among these, tetramethoxysilane and tetraethoxysilane are particularly preferable.

[0040] The area ratio of the components (b-1), (b-2), and (b-3) in the GPC elution curve of the component (b) can be controlled by the amount of coupling agent added, the temperature, and the time in the coupling reaction, as described above. This makes it possible to control the weight average molecular weight of each of the components (b-1), (b-2), and (b-3) and the content of each of the components. Specifically, when the coupling agent is an alkoxysilane compound, the time from when the reaction temperature reaches the maximum temperature until the coupling agent is added is set to 1 to 30 minutes, the reaction time of the coupling agent is set to 1 to 60 minutes, the reaction temperature is set to 55 to 100°C, and the amount of coupling agent added is adjusted so that the molar ratio to the total number of moles of the polymerization initiator is 0.025 to 0.30. In addition, when the coupling agent is other than an alkoxysilane compound, the time from when the reaction temperature reaches the maximum temperature until the coupling agent is added is set to 1 to 30 minutes, the reaction time of the coupling agent is set to 1 to 35 minutes, the reaction temperature is set to 50 to 95°C, and the amount of the coupling agent added is adjusted so that the molar ratio to the total number of moles of the polymerization initiator is 0.025 to 0.20.

[0041] (Hydrogenation reaction) In the block copolymer composition of the present embodiment, a part or all of the unsaturated double bonds derived from the conjugated diene compounds of component (a) and component (b) are hydrogenated. The hydrogenation method is not particularly limited, and can be carried out using a known technique using a hydrogenation catalyst.

[0042] The hydrogenation catalyst is not particularly limited, and a known catalyst can be used. For example, a supported heterogeneous hydrogenation catalyst in which a metal such as Ni, Pt, Pd, Ru, etc. is supported on carbon, silica, alumina, diatomaceous earth, etc.; a so-called Ziegler type hydrogenation catalyst which uses a transition metal salt such as an organic acid salt or an acetylacetone salt of Ni, Co, Fe, Cr, etc. and a reducing agent such as an organoaluminum; or a homogeneous hydrogenation catalyst such as a so-called organometallic complex of an organometallic compound of Ti, Ru, Rh, Zr, etc. can be used.

[0043] Specifically, the hydrogenation catalysts described in JP-B-42-8704, JP-B-43-6636, JP-B-63-4841, JP-B-1-37970, JP-B-1-53851, and JP-B-2-9041 can be used. Among these, preferred hydrogenation catalysts include titanocene compounds, reducing organometallic compounds, or mixtures thereof.

[0044] The titanocene compound is not particularly limited, but examples thereof include compounds described in JP-A-8-109219. Specific examples thereof include compounds having at least one ligand having a (substituted) cyclopentadienyl skeleton, an indenyl skeleton, or a fluorenyl skeleton, such as biscyclopentadienyl titanium dichloride and monopentamethylcyclopentadienyl titanium trichloride.

[0045] The reducing organometallic compound is not particularly limited, but examples thereof include organoalkali metal compounds such as organolithium compounds, organomagnesium compounds, organoaluminum compounds, organoboron compounds, and organozinc compounds.

[0046] The hydrogenation reaction temperature is preferably 0 to 200° C., more preferably 30 to 150° C. The hydrogen pressure used in the hydrogenation reaction is preferably 0.1 to 15 MPa, more preferably 0.2 to 10 MPa, and even more preferably 0.3 to 5 MPa. The hydrogenation reaction time is preferably 3 minutes to 10 hours, and more preferably 10 minutes to 5 hours. The hydrogenation reaction may be a batch process, a continuous process, or a combination thereof.

[0047] The block copolymer composition can be obtained by removing catalyst residues, if necessary, from the block copolymer solution obtained through the hydrogenation reaction and separating the solution. The method for separating the solvent is not particularly limited, but examples thereof include a method in which a polar solvent that is a poor solvent for the hydrogenated block copolymer, such as acetone or alcohol, is added to the reaction solution after hydrogenation to precipitate and recover the polymer, a method in which the reaction solution after hydrogenation is poured into boiling water with stirring and the solvent is removed and recovered by steam stripping, and a method in which the reaction solution after hydrogenation is heated to distill off the solvent.

[0048] The amount (% by mass) of the polymer block (A) relative to the total amount (100% by mass) of vinyl aromatic monomer units used to polymerize the block copolymer, i.e., the block ratio, is preferably 90% by mass or more, more preferably 95% by mass or more, and even more preferably 97% by mass or more. When the block ratio is within the above range, a block copolymer composition having excellent finishability tends to be obtained, and a pressure-sensitive adhesive composition containing this block copolymer composition tends to have excellent adhesion and holding power.

[0049] The amount (% by mass) of the polymer block (A), that is, the block ratio, can be calculated by calculating the block styrene content and dividing it by the total amount of vinyl aromatic monomer units as described below. That is, the block copolymer before hydrogenation is dissolved in chloroform, and an osmonic acid / tertiary butyl hydroperoxide solution is added to cleave the double bonds of the butadiene component. Next, methanol is added, and the mixture is filtered. The residue is dissolved in chloroform, and the resulting solution is measured with an ultraviolet spectrophotometer to calculate the block styrene content from the peak intensity (absorption wavelength: 262 nm).

[0050] In the method for producing the block copolymer composition of the present embodiment, a step of deashing metals derived from the polymerization initiator, etc. may be employed as necessary. In addition, in the method for producing the block copolymer composition of the present embodiment, a step of adding an antioxidant, a neutralizing agent, a surfactant, etc. may be further employed as necessary. The antioxidant is not particularly limited, but examples thereof include hindered phenol compounds, phosphorus compounds, and sulfur compounds similar to those described below. The neutralizing agent is not particularly limited, but examples thereof include various metal stearates, hydrotalcite, benzoic acid, and the like. The surfactant is not particularly limited, but examples thereof include anionic surfactants, nonionic surfactants, cationic surfactants, etc. The anionic surfactant is not particularly limited, but examples thereof include fatty acid salts, alkyl sulfate ester salts, alkylaryl sulfonate salts, etc. The nonionic surfactant is not particularly limited, but examples thereof include polyoxyethylene alkyl ethers, polyoxyethylene alkylaryl ethers, etc. Furthermore, the cationic surfactant is not particularly limited, but examples thereof include alkylamine salts, quaternary ammonium salts, etc.

[0051] The block copolymer composition of the present embodiment that can be produced as described above may contain a so-called modified block copolymer in which a polar group-containing functional group containing an atom selected from nitrogen, oxygen, silicon, phosphorus, sulfur, and tin is bonded to the block copolymer, or a modified block copolymer in which a block copolymer component is modified with a modifier such as maleic anhydride. Such a modified block copolymer can be obtained by subjecting component (a) and component (b) to a known modification reaction.

[0052] The method for imparting these functional groups is not particularly limited, but examples thereof include a method in which a functional group is added to a polymer using a compound having a functional group in an initiator, a monomer, a coupling agent, or a terminator.

[0053] As the initiator containing a functional group, an initiator containing an N group is preferable, and examples thereof include dioctylaminolithium, di-2-ethylhexylaminolithium, ethylbenzylaminolithium, (3-(dibutylamino)-propyl)lithium, and piperidinolithium.

[0054] In addition, examples of monomers containing functional groups include compounds containing a hydroxyl group, an acid anhydride group, an epoxy group, an amino group, an amide group, a silanol group, or an alkoxysilane group in the monomers used in the above-mentioned polymerization. Among these, monomers containing an N group are preferred, and examples thereof include N,N-dimethylvinylbenzylamine, N,N-diethylvinylbenzylamine, N,N-dipropylvinylbenzylamine, N,N-dibutylvinylbenzylamine, N,N-diphenylvinylbenzylamine, 2-dimethylaminoethylstyrene, 2-diethylaminoethylstyrene, 2-bis(trimethylsilyl)aminoethylstyrene, 1-(4-N,N-dimethylaminophenyl)-1-phenylethylene, Examples of the styrene-based copolymer include N,N-dimethyl-2-(4-vinylbenzyloxy)ethylamine, 4-(2-pyrrolidinoethyl)styrene, 4-(2-piperidinoethyl)styrene, 4-(2-hexamethyleneiminoethyl)styrene, 4-(2-morpholinoethyl)styrene, 4-(2-thiazinoethyl)styrene, 4-(2-N-methylpiperazinoethyl)styrene, 1-((4-vinylphenoxy)methyl)pyrrolidine, and 1-(4-vinylbenzyloxymethyl)pyrrolidine.

[0055] Furthermore, the coupling agent and the terminator containing a functional group include, among the above-mentioned coupling agents, compounds containing hydroxyl groups, acid anhydride groups, epoxy groups, amino groups, amide groups, silanol groups, and alkoxysilane groups. Among these, coupling agents containing N groups or O groups are preferred, and examples thereof include tetraglycidyl metaxylenediamine, tetraglycidyl-1,3-bisaminomethylcyclohexane, tetraglycidyl-p-phenylenediamine, tetraglycidyl diaminodiphenylmethane, diglycidylaniline, γ-caprolactone, γ-glycidoxyethyl trimethoxysilane, γ-glycidoxypropyl trimethoxysilane, γ-glycidoxypropyl triphenoxysilane, γ-glycidoxypropyl methyl dimethoxysilane, γ-glycidoxypropyl diethylethoxysilane, 1,3-dimethyl-2-imidazolidinone, 1,3-diethyl-2-imidazolidinone, N,N'-dimethylpropyleneurea, and N-methylpyrrolidone.

[0056] After producing the block copolymers of components (a) and (b) constituting the block copolymer of the present embodiment as described above, the block copolymer is isolated, i.e., finished, by the method described below to obtain a block copolymer composition. When the polymerization step of components (a) and (b) is carried out in an inert hydrocarbon solvent, the inert hydrocarbon solvent is removed to isolate the block copolymer. A specific method for removing the solvent includes steam stripping. A water-containing crumb is obtained by steam stripping, and the obtained water-containing crumb is dried to obtain a block copolymer composition.

[0057] In steam stripping, it is preferable to use a surfactant as a crumb forming agent. Such surfactants are not particularly limited, but examples thereof include the same anionic surfactants, cationic surfactants, and nonionic surfactants as described above. These surfactants can generally be added to the water in the stripping zone in an amount of 0.1 to 3000 ppm. In addition to surfactants, water-soluble salts of metals such as Li, Na, Mg, Ca, Al, and Zn can also be used as crumb dispersion aids.

[0058] The concentration of the crumb-like block copolymer dispersed in water obtained through the block copolymer polymerization step and the steam stripping is generally 0.1 to 20% by mass (ratio to the water in the stripping zone). Within this range, crumbs having good particle size can be obtained without causing operational problems. It is preferable to adjust the moisture content of the block copolymer crumbs to 1 to 30% by mass by dehydration, and then dry the crumbs until the moisture content is 1% by mass or less.

[0059] In the dehydration step of the crumbs, dehydration may be performed using a compression water wringer such as a roll, a Banbury type dehydrator, or a screw extruder type wringer dehydrator, or dehydration and drying may be performed simultaneously using a conveyer or a box-type hot air dryer.

[0060] [Adhesive composition] The pressure-sensitive adhesive composition of the present embodiment contains the above-mentioned block copolymer composition, a tackifier, and a softener. The content of the tackifier in the pressure-sensitive adhesive composition is 1 to 250 parts by mass relative to 100 parts by mass of the block copolymer composition, and the content of the softener is 120 parts by mass or less relative to 100 parts by mass of the block copolymer composition. This makes it possible to obtain a pressure-sensitive adhesive composition having high holding power, low viscosity, and an excellent balance between holding power and viscosity. The pressure-sensitive adhesive composition of the present embodiment may contain other components described below as necessary. From the viewpoint of obtaining a pressure-sensitive adhesive composition having higher holding power, the content of the tackifier is preferably 1 to 200 parts by mass, more preferably 1 to 150 parts by mass, and even more preferably 1 to 130 parts by mass, relative to 100 parts by mass of the block copolymer composition. From the same viewpoint, the content of the softener is preferably 80 parts by mass or less, and more preferably 50 parts by mass or less, relative to 100 parts by mass of the block copolymer composition.

[0061] In addition, when other polymers such as a styrene-butadiene block copolymer, a styrene-isoprene block copolymer, a hydrogenated styrene-butadiene block copolymer, or a hydrogenated styrene-isoprene block copolymer other than the above-mentioned block copolymer composition are added to the pressure-sensitive adhesive composition of the present embodiment, it is preferable that the pressure-sensitive adhesive composition contains 1 to 250 parts by mass of a tackifier described later and 0 to 120 parts by mass of a softener described later relative to 100 parts by mass of the total content of the other polymers and the above-mentioned components (a) and (b).

[0062] (tackifier) A wide variety of tackifiers can be selected depending on the application and required performance of the resulting pressure-sensitive adhesive composition. The tackifier is not particularly limited, but examples thereof include rosin-based compounds such as natural rosin, modified rosin, glycerol ester of natural rosin, glycerol ester of modified rosin, pentaerythritol ester of natural rosin, pentaerythritol ester of modified rosin, hydrogenated rosin, and pentaerythritol ester of hydrogenated rosin; copolymers of natural terpene, three-dimensional polymers of natural terpene, aromatic modified terpene resins, hydrogenated derivatives of aromatic modified terpene resins, terpene phenol resins, hydrogenated derivatives of terpene phenol resins, terpene resins (monoterpene, diterpene, tri ... Examples of such resins include terpene-based compounds such as aliphatic petroleum hydrocarbon resins (C5 resins), hydrogenated derivatives of aliphatic petroleum hydrocarbon resins, aromatic petroleum hydrocarbon resins (C9 resins), hydrogenated derivatives of aromatic petroleum hydrocarbon resins, dicyclopentadiene resins, hydrogenated derivatives of dicyclopentadiene resins, C5 / C9 copolymer resins, hydrogenated derivatives of C5 / C9 copolymer resins, cyclic aliphatic petroleum hydrocarbon resins, and hydrogenated derivatives of cyclic aliphatic petroleum hydrocarbon resins, and aromatic group-containing resins. These tackifiers may be used alone or in combination of two or more. The C5 / C9 copolymer system is a copolymerized petroleum resin polymerized using a mixture of C5 fraction and C9 fraction as raw material. As the tackifier, a liquid type tackifier that is colorless to pale yellow, substantially odorless, and has good thermal stability can also be used. Preferred tackifiers depending on applications and performance will be described in more detail below.

[0063] <Hydrogenated derivative tackifier> From the viewpoints of suppressing coloration and reducing odor, the tackifier is preferably a hydrogenated derivative. The hydrogenated derivative is not particularly limited, but examples thereof include hydrogenated derivatives of aromatic modified terpene resins, hydrogenated derivatives of terpene phenol resins, hydrogenated derivatives of hydrogenated terpene resins, hydrogenated derivatives of aliphatic petroleum hydrocarbon resins (C5 resins), hydrogenated derivatives of aromatic petroleum hydrocarbon resins (C9 resins), hydrogenated derivatives of dicyclopentadiene resins, hydrogenated derivatives of C5 / C9 copolymer resins, and hydrogenated derivatives of cyclic aliphatic petroleum hydrocarbon resins. Among these, hydrogenated derivatives of aromatic petroleum hydrocarbon resins (C9 resins), hydrogenated derivatives of dicyclopentadiene resins, and hydrogenated derivatives of hydrogenated terpene resins are particularly preferred. Commercially available hydrogenated derivatives of this kind include, but are not limited to, the Arkon P and M series (product names) manufactured by Arakawa Chemical Industry Co., Ltd., the Imav S and P series manufactured by Idemitsu Kosan Co., Ltd., the Escolez 5000 series (product name) manufactured by ExxonMobil Chemical Co., Ltd., and the Clearon P series manufactured by Yasuhara Chemical Co., Ltd.

[0064] <Tackifiers other than hydrogenated derivatives> Examples of tackifiers other than hydrogenated derivatives include, but are not limited to, natural rosin, modified rosin, glycerol ester of natural rosin, glycerol ester of modified rosin, pentaerythritol ester of natural rosin, pentaerythritol ester of modified rosin, hydrogenated rosin, pentaerythritol ester of hydrogenated rosin; copolymers of natural terpene, three-dimensional polymers of natural terpene, aromatic modified terpene resins, terpene phenol resins, terpene resins, hydrogenated terpene resins; aliphatic petroleum hydrocarbon resins (C5 resins), aromatic petroleum hydrocarbon resins (C9 resins), dicyclopentadiene resins, C5 / C9 copolymer resins, and cyclic aliphatic petroleum hydrocarbon resins. Among these, aliphatic petroleum hydrocarbon resins (C5 resins), aromatic petroleum hydrocarbon resins (C9 resins), C5 / C9 copolymer resins, cyclic aliphatic petroleum hydrocarbon resins, terpene resins, natural and modified rosin esters, and mixtures thereof are preferred. Commercially available products include aliphatic petroleum hydrocarbon resins (C5 resins) such as the Quinton 100 series (product name) manufactured by Zeon Corporation, the Escorez 1000 series manufactured by ExxonMobil Chemical Corporation, and the WING TACK series (product name) manufactured by Cray Valley; aromatic petroleum hydrocarbon resins (C9 resins); C5 / C9 copolymer resins such as the PICCOTAC series (product name) manufactured by Eastman Chemical Company, the Escorez 2000 series (product name) manufactured by ExxonMobil Chemical Company, and the FTR series (product name) manufactured by Mitsui Chemicals, Inc.; terpene resins and natural and modified rosin esters such as the SYLVALITE series and SYLVARES series (product name) manufactured by Arizona Chemical Company, and the PICCOLYTE series (product name) manufactured by PINOVA Corporation.

[0065] <Aliphatic tackifier> From the viewpoint of obtaining a pressure-sensitive adhesive composition having high adhesion and high holding power, and from the viewpoint of economy, it is preferable to use an aliphatic tackifier as the tackifier. The aliphatic tackifier is not particularly limited, but examples thereof include aliphatic petroleum hydrocarbon resins (C5 resins), hydrogenated derivatives of aliphatic petroleum hydrocarbon resins (C5 resins), C5 / C9 copolymer resins, and hydrogenated derivatives of C5 / C9 copolymer resins. The aliphatic tackifier refers to a tackifier having an aliphatic hydrocarbon group content of preferably 50% by mass or more, more preferably 70% by mass or more, even more preferably 80% by mass or more, even more preferably 88% by mass or more, and even more preferably 95% by mass or more. By having the aliphatic hydrocarbon group content within the above range, adhesion, holding power, and economy tend to be further improved.

[0066] The aliphatic tackifier can be produced by homopolymerizing or copolymerizing a monomer having an aliphatic group and a polymerizable unsaturated group. Monomers having aliphatic groups and polymerizable unsaturated groups include, but are not limited to, natural and synthetic terpenes containing C5 or C6 cyclopentyl or cyclohexyl groups.Other monomers that can be used in copolymerization include, but are not limited to, 1,3-butadiene, cis-1,3-pentadiene, trans-1,3-pentadiene, 2-methyl-1,3-butadiene, 2-methyl-2-butene, cyclopentadiene, dicyclopentadiene, terpene, terpene-phenol resins, etc.

[0067] <Aromatic tackifier> From the viewpoint of obtaining a pressure-sensitive adhesive composition having high adhesive strength and high coatability, it is preferable to use an aromatic tackifier as the tackifier. The aromatic tackifier is not particularly limited, but examples thereof include aromatic petroleum hydrocarbon resins (C9 resins) and C5 / C9 copolymer resins. The aromatic tackifier refers to a tackifier having an aromatic hydrocarbon group content of preferably 50% by mass or more, more preferably 70% by mass or more, even more preferably 80% by mass or more, even more preferably 88% by mass or more, and even more preferably 95% by mass or more. By having the aromatic hydrocarbon group content within the above range, adhesive strength and coatability tend to be further improved.

[0068] The aromatic tackifier can be produced by homopolymerizing or copolymerizing a monomer having an aromatic group and a polymerizable unsaturated group. Monomers having an aromatic group and a polymerizable unsaturated group are not particularly limited, but include, for example, styrene, α-methylstyrene, vinyltoluene, methoxystyrene, tert-butylstyrene, chlorostyrene, and indene monomers (including methylindene).Other monomers that can be used in copolymerization are not particularly limited, but include, for example, 1,3-butadiene, cis-1,3-pentadiene, trans-1,3-pentadiene, 2-methyl-1,3-butadiene, 2-methyl-2-butene, cyclopentadiene, dicyclopentadiene, terpene, and terpene-phenol resins.

[0069] <Tackifier having affinity with blocks of the glass phase (e.g., polymer block (A)) and / or the non-glass phase (e.g., polymer block (B)) of the block copolymer> From the viewpoints of high adhesive strength, inhibition of change in adhesive strength over time, or creep performance (the smaller the value, the better), it is more preferable that the pressure-sensitive adhesive composition of the present embodiment contains 20 to 75 mass % of a tackifier having affinity for a non-glass phase block (usually a middle block) of the block copolymer, and 3 to 30 mass % of a tackifier having affinity for a glass phase block (usually an outer block) of the block copolymer. The block copolymer as used herein means to include the above-mentioned components (a) and (b).

[0070] The tackifier having affinity for the block of the glass phase of the block copolymer is not particularly limited, but for example, a resin having an aromatic ring between molecules is preferable. Such a resin is not particularly limited, but for example, an aromatic group-containing resin such as a homopolymer or copolymer containing vinyltoluene, styrene, α-methylstyrene, coumarone, or indene as a structural unit is preferable. Furthermore, among these, Kristalex and Plastolyn (trade name, manufactured by Eastman Chemical Co.) having α-methylstyrene are preferable.

[0071] The content of the tackifier having affinity to the block of the glass phase of the block copolymer is preferably 3 to 30 mass%, more preferably 5 to 20 mass%, and even more preferably 6 to 12 mass%, relative to 100 mass% of the pressure-sensitive adhesive composition of the present embodiment.

[0072] From the viewpoints of high initial adhesive strength, high wettability, low melt viscosity of the adhesive composition, high coatability, etc., it is preferable to use a petroleum resin having an aroma content of 3 to 12 mass% as a tackifier. Such petroleum resins are not particularly limited, but examples thereof include aliphatic petroleum hydrocarbon resins (C5 resins), hydrogenated derivatives of aliphatic petroleum hydrocarbon resins (C5 resins), aromatic petroleum hydrocarbon resins (C9 resins), hydrogenated derivatives of aromatic petroleum hydrocarbon resins (C9 resins), dicyclopentadiene resins, hydrogenated derivatives of dicyclopentadiene resins, C5 / C9 copolymer resins, hydrogenated derivatives of C5 / C9 copolymer resins, cyclic aliphatic petroleum hydrocarbon resins, and hydrogenated derivatives of cyclic aliphatic petroleum hydrocarbon resins. The aroma content of the petroleum resin is preferably 3 to 12 mass%, more preferably 4 to 10 mass%. Among these, hydrogenated petroleum resins are particularly preferable.

[0073]

[0133] In the pressure-sensitive adhesive composition of the present embodiment, the content of the tackifier is 1 to 250 parts by mass relative to 100 parts by mass of the above-mentioned block copolymer composition, and can be selected in a wide variety of ways within this range depending on the application and required performance of the resulting pressure-sensitive adhesive composition.

[0074] (Softener) The term "softener" refers to a substance that has the function of lowering the hardness and viscosity of the pressure-sensitive adhesive composition. The softener is not particularly limited, but examples thereof include oils, plasticizers, synthetic liquid oligomers, and mixtures thereof. The softeners that are preferable depending on the application and performance will be described in more detail below.

[0075] From the viewpoint of reducing the viscosity, improving the adhesion, and reducing the hardness of the adhesive composition of the present embodiment, oils can be used as the softener. The oils are not particularly limited, but examples thereof include known paraffin-based process oils, naphthene-based process oils, aromatic process oils, and mixed oils thereof.

[0076] The plasticizer is not particularly limited, but examples thereof include liquid paraffin; fatty acid esters consisting of higher fatty acids having 12 to 16 carbon atoms, such as isopropyl myristate, ethyl laurate, and isopropyl palmitate, and lower monohydric alcohols having 1 to 4 carbon atoms; fatty acids having 8 to 10 carbon atoms; glycols such as ethylene glycol, diethylene glycol, triethylene glycol, polyethylene glycol, propylene glycol, and polypropylene glycol; oils and fats such as olive oil, castor oil, squalene, and lanolin; ethyl acetate, ethyl alcohol, etc. Organic solvents such as dimethyldecyl sulfoxide, decyl methyl sulfoxide, dimethyl sulfoxide, dimethylformamide, dimethylacetamide, dimethyllaurylamide, dodecylpyrrolidone, isosorbitol, oleyl alcohol, and lauric acid; liquid surfactants; ethoxylated stearyl alcohol, glycerin esters, isotridecyl myristate, N-methylpyrrolidone, ethyl oleate, oleic acid, diisopropyl adipate, octyl palmitate, 1,3-propanediol, and glycerin. Of these, compounds that are liquid at room temperature are used. The plasticizers may be used alone or in combination of two or more kinds.

[0077] Among the plasticizers, glycerin esters are preferred, and medium-chain fatty acid triglycerides, which are esters of fatty acids having 8 to 10 carbon atoms and glycerin, are more preferred. Examples of medium-chain fatty acid triglycerides include tri(caprylic acid / capric acid)glyceryl.

[0078] When the pressure-sensitive adhesive tape using the pressure-sensitive adhesive composition of the present embodiment is used as a medical pressure-sensitive adhesive tape such as a taping tape, it is preferable to use liquid paraffin and other liquid plasticizers in combination as the plasticizer.

[0079] When it is desired to make the pressure-sensitive adhesive composition of the present embodiment softer, from the viewpoint of improving bleeding properties, it is preferable to use a synthetic liquid oligomer as the softener. The synthetic liquid oligomer is not particularly limited, but examples thereof include styrene oligomer, butadiene oligomer, isoprene oligomer, butene oligomer, etc.

[0080]

[0043] Examples of commercially available softeners for use in the pressure-sensitive adhesive composition of the present embodiment are not particularly limited, and include, for example, Diana Fresia S32 (trade name), Diana Process Oil PW-90 (trade name), Process Oil NS100 (trade name), Process Oil NS90S (trade name) manufactured by Idemitsu Kosan Co., Ltd., White Oil Broom350 (trade name), DN Oil KP-68 (trade name) manufactured by Kukdong Oil & Chem Co., Ltd., Enerper M1930 (trade name) manufactured by BP Chemicals Co., Ltd., Kaydol (trade name) manufactured by Crompton Corporation, Primol352 (trade name) manufactured by Esso Corporation, and KN4010 (trade name) manufactured by PetroChina Company.

[0081] (Other Ingredients) The pressure-sensitive adhesive composition of the present embodiment may contain other components, such as an antioxidant, a polymer other than the components (a) and (b), a wax, a stabilizer such as a light stabilizer, and other additives, as necessary.

[0082] <Antioxidants> Examples of the antioxidant include, but are not limited to, 2,6-di-t-butyl-4-methylphenol, n-octadecyl-3-(4'-hydroxy-3',5'-di-t-butylphenyl)propionate, 2,2'-methylenebis(4-methyl-6-t-butylphenol), 2,2'-methylenebis(4-ethyl-6-t-butylphenol), 2,4-bis[(octylthio)methyl]-0-cresol, 2-t-butyl-6-(3-t-butyl-2-hydroxy-5-methylbenzyl)-4-methylphenylacrylate, 2,4-di-t-butylphenyl acrylate, and the like. Examples of the antioxidants include hindered phenol-based antioxidants such as myl-6-[1-(3,5-di-t-amyl-2-hydroxyphenyl)ethyl]phenyl acrylate and 2-[1-(2-hydroxy-3,5-di-tert-pentylphenyl)]acrylate; sulfur-based antioxidants such as dilauryl thiodipropionate, lauryl stearyl thiodipropionate pentaerythritol-tetrakis(β-lauryl thiopropionate); and phosphorus-based antioxidants such as tris(nonylphenyl)phosphite and tris(2,4-di-t-butylphenyl)phosphite.

[0083] Examples of commercially available antioxidants include Sumilizer GM (trade name), Sumilizer TPD (trade name), and Sumilizer TPS (trade name) manufactured by Sumitomo Chemical Co., Ltd., Irganox 1010 (trade name), Irganox HP2225FF (trade name), Irgafos 168 (trade name), and Irganox 1520 (trade name) manufactured by Ciba Specialty Chemicals, and JF77 (trade name) manufactured by Johoku Chemical Co., Ltd. These stabilizers may be used alone or in combination of two or more.

[0084] The content of the antioxidant is arbitrary, but is preferably 5 parts by mass or less relative to 100 parts by mass of the pressure-sensitive adhesive composition.

[0085] <Polymers other than component (a) and component (b)> The polymer other than the component (a) and the component (b) is not particularly limited, but may be, for example, a polyolefin copolymer, a vinyl aromatic copolymer, or other rubber. In this specification, "other than the component (a) and the component (b)" means that it does not fall under either the component (a) or the component (b).

[0086] The polyolefin copolymer is not particularly limited, but examples thereof include atactic polypropylene, ethylene-ethyl acrylate copolymer, α-olefin polymer, and the like.

[0087] The vinyl aromatic copolymer is not particularly limited, but examples thereof include styrene-ethylene block copolymers, styrene-butadiene block copolymers, styrene-propylene block copolymers, styrene-isoprene block copolymers, styrene-butadiene-isoprene block copolymers, styrene-butadiene / isoprene block copolymers, hydrogenated styrene-butadiene block copolymers, hydrogenated styrene-isoprene block copolymers, hydrogenated styrene-butadiene-isoprene block copolymers, hydrogenated styrene-butadiene / isoprene block copolymers, etc., which are polymers other than component (a) and component (b). The vinyl aromatic copolymer may be a vinyl aromatic thermoplastic resin or a vinyl aromatic elastomer. The content of the vinyl aromatic copolymer other than the component (a) and the component (b) is preferably 10 to 80 parts by mass, more preferably 10 to 70 parts by mass, even more preferably 10 to 60 parts by mass, and still more preferably 20 to 50 parts by mass, relative to 100 parts by mass in total of the polymer other than the component (a) and the component (b) and the component (a) and the component (b).

[0088] Examples of other rubbers include, but are not limited to, natural rubber; and synthetic rubbers such as isoprene-isoprene rubber, polyisoprene rubber, polybutadiene rubber, styrene-butadiene rubber, styrene-isoprene rubber, propylene-butylene rubber, ethylene-propylene rubber, chloroprene rubber, acrylic rubber, isoprene-isobutylene rubber, and polypentenamer rubber.

[0089] Hereinafter, preferred polymers other than the components (a) and (b) depending on the application and performance of the pressure-sensitive adhesive composition of the present embodiment will be described in more detail.

[0090] [Hydrogenated vinyl aromatic copolymer]

[0113] In cases where reduction in adhesive residue when the pressure-sensitive adhesive composition of the present embodiment is peeled off, inhibition of change in adhesive strength over time or creep properties (the smaller the value, the better), thermal stability, light resistance, and the like are required, a hydrogenated vinyl aromatic copolymer can be used as the above-mentioned "polymer other than component (a) and component (b)". The hydrogenated vinyl aromatic copolymer is not particularly limited, but examples thereof include hydrogenated styrene-butadiene block copolymers having a structure such as S-EB-S (S: polystyrene block, EB: ethylene / butylene copolymer block); hydrogenated styrene-isoprene block copolymers having a structure such as S-EP-S (S: polystyrene block, EP: ethylene / propylene copolymer block), and hydrogenated styrene-butadiene-isoprene block copolymers having a structure such as SE-EP-S (S: polystyrene block, E: ethylene block, EP: ethylene / propylene copolymer block).

[0091] The styrene content of the hydrogenated vinyl aromatic copolymer is preferably 10% by mass to 45% by mass relative to 100% by mass of the hydrogenated vinyl aromatic copolymer. The hydrogenation rate of the unsaturated groups in the conjugated diene in the hydrogenated vinyl aromatic copolymer is preferably 30 mol% or more, more preferably 50 mol% or more, even more preferably 70 mol% or more, and even more preferably 85 mol% or more.

[0092] [Isoprene block copolymer]

[0113] When high adhesion or inhibition of gelation is required for the pressure-sensitive adhesive composition of the present embodiment, an isoprene-based block copolymer having an isoprene monomer unit can be used as the above-mentioned "polymer other than component (a) and component (b)". The isoprene-based block copolymer is not particularly limited, but for example, (SI) n , (SI) n -S, (SI) n Styrene-isoprene block copolymers having structures such as Y (S: polystyrene block, I: polyisoprene block); (SIB) n , (SI-B) n -S, (SIB) n Y (S: polystyrene block, I: polyisoprene block, B: polybutadiene block, Y: residue of a polyfunctional coupling agent or residue of a polymerization initiator, n is an integer of 1 or more, preferably an integer of 1 to 5), or (SI / B) n , (SI / B) n -S, (SI / B) n Examples of such block copolymers include styrene-butadiene-isoprene block copolymers having a structure such as Y (S: polystyrene block, I / B: isoprene / butadiene copolymer block, Y: a residue of a coupling agent or a residue of a polymerization initiator, n is an integer of 1 or more, preferably an integer of 1 to 5). These preferably have a radial structure.

[0093] [Ionomer] In the case where the adhesive composition of the present embodiment requires high low-temperature coatability, creep (the smaller the value, the better), high strength or high elongation, the above-mentioned "polymer other than component (a) and component (b)" may be used in the form of an ionomer. The ionomer is not particularly limited, but is preferably, for example, a homopolymer or copolymer containing a carboxylate, sulfonate or phosphonate that is neutralized or partially neutralized by a metal ion. The content of the ionomer is preferably 5 mass% or less with respect to the total amount of the adhesive composition.

[0094] [Polyolefin copolymer]

[0113] In the case where the pressure-sensitive adhesive composition of the present embodiment requires high-temperature storage stability, high elongation, or a reduced amount of tackifier in the block copolymer composition (55 mass % or less, further 45 mass % or less in the composition), a polyolefin-based copolymer can be used as the above-mentioned "polymer other than component (a) and component (b)". The polyolefin copolymer is not particularly limited, but for example, a copolymer of α-olefin and olefin, or a propylene homopolymer is preferable. The melting point of these polymers (conditions: DSC measurement, 5°C / min) is preferably 110°C or less, more preferably 100°C or less, and further preferably 60°C to 90°C. These polymers may be thermoplastic resins or elastomers. The molecular weight distribution of these polymers is preferably 1 to 4, more preferably 1 to 3.

[0095] From the viewpoint of processability, it is more preferable to use two or more types of copolymers using α-olefins or propylene homopolymers in combination. Specifically, it is preferable to use a polymer having a weight average molecular weight of 30,000 to 60,000 in combination with a polymer having a weight average molecular weight of 60,000 to 90,000, and it is more preferable to use a polymer having a weight average molecular weight of 35,000 to 55,000 in combination with a polymer having a weight average molecular weight of 60,000 to 80,000. In addition, the liquid component (oil, etc.) in the pressure-sensitive adhesive composition using these is preferably 20 mass % or more, more preferably 25 mass % or more.

[0096] [Conjugated diene rubber] When the adhesive composition of the present embodiment is used as a composition for an adhesive tape to improve its own backside adhesive strength or skin adhesion, a conjugated diene rubber can be used as the above-mentioned "polymer other than component (a) and component (b)". The conjugated diene rubber is not particularly limited, but examples thereof include isoprene-isobutylene rubber, polyisoprene rubber, polybutadiene rubber, styrene-butadiene rubber, styrene-isoprene rubber, and propylene-butylene rubber. Among these, polyisoprene rubber is more preferable from the viewpoint of high effectiveness. The content of the conjugated diene rubber is preferably 3 mass% or more and 25 mass% or less, more preferably 5 mass% or more and 20 mass% or less, and even more preferably 5 mass% or more and 15 mass% or less, relative to the total amount of the pressure-sensitive adhesive composition. By having a conjugated diene rubber content of 3% by mass or more, the adhesive strength to the back surface and the adhesive strength to the skin tend to be improved, while by having a conjugated diene rubber content of 25% by mass or less, the cohesive strength tends to be improved and adhesive residue tends to be suppressed.

[0097] [Olefin elastomer] When elongation and the like is required for the pressure-sensitive adhesive composition of this embodiment, it is preferable to use an olefin-based elastomer in combination as the above-mentioned "polymer other than component (a) and component (b)". The olefin-based elastomer is not particularly limited, but is preferably one having a Tg of, for example, −10° C. or less. From the viewpoint of creep performance (the smaller the value, the better), an olefin-based elastomer having blocks is more preferable.

[0098] <Wax> The pressure-sensitive adhesive composition of the present embodiment may contain a wax as necessary. The wax is not particularly limited, but for example, paraffin wax, microcrystalline wax, low molecular weight polyethylene wax, etc. can be added. When a pressure-sensitive adhesive composition is required to have a low melt viscosity, particularly a low melt viscosity at 140° C. or less, it is preferable to use at least one wax selected from paraffin wax, microcrystalline wax, and Fischer-Tropsch wax in combination. The content of the wax is preferably 2 to 10% by mass, more preferably 5 to 10% by mass. The melting point of the wax is preferably 50° C. to 110° C., more preferably 65° C. to 110° C., even more preferably 70° C. to 110° C., and even more preferably 75° C. to 110° C. The softening point of the tackifier used in combination is preferably 70° C. or higher, more preferably 80° C. or higher. The G' (measurement conditions: 25° C., 10 rad / s) of the obtained pressure-sensitive adhesive composition is preferably 1 MPa or lower. The crystallization temperature of the pressure-sensitive adhesive composition is preferably 7° C. or lower.

[0099] <Light stabilizer> The pressure-sensitive adhesive composition of the present embodiment may contain a light stabilizer, if necessary. The light stabilizer is not particularly limited, but examples thereof include benzotriazole-based ultraviolet absorbers such as 2-(2'-hydroxy-5'-methylphenyl)benzotriazole, 2-(2'-hydroxy-3',5'-t-butylphenyl)benzotriazole, and 2-(2'-hydroxy-3',5'-di-t-butylphenyl)-5-chlorobenzotriazole; benzophenone-based ultraviolet absorbers such as 2-hydroxy-4-methoxybenzophenone; and hindered amine-based light stabilizers.

[0100] <Fine particle filler> The pressure-sensitive adhesive composition of the present embodiment may further contain a fine particle filler as another additive. The particulate filler may be any commonly used one, and is not particularly limited.The particulate filler is not particularly limited, and examples thereof include mica, calcium carbonate, kaolin, talc, titanium oxide, diatomaceous earth, urea resin, styrene beads, calcined clay, starch, etc.These are preferably spherical in shape, and their dimensions (diameter in the case of spheres) are not particularly limited.

[0101] [Characteristics of the adhesive composition] The performance of the pressure-sensitive adhesive composition of the present embodiment can be measured using a pressure-sensitive adhesive tape produced under the conditions shown in the examples described below, according to the measurement conditions shown in the examples.

[0102] [Method for producing pressure-sensitive adhesive composition]

[0133] The pressure-sensitive adhesive composition of the present embodiment can be produced by mixing the above-mentioned block copolymer composition, a tackifier, a softener, and, as necessary, other additives by a known method. The mixing method is not particularly limited, but may be, for example, a method in which the block copolymer composition, the tackifier, and the softener are uniformly mixed while being heated in a mixer or kneader. The temperature during mixing is preferably 130° C. to 210° C., more preferably 135° C. to 200° C., and even more preferably 140° C. to 190° C. When the temperature during mixing is 130° C. or higher, the block copolymer composition tends to be sufficiently melted and dispersed well. Furthermore, when the temperature during mixing is 210° C. or lower, evaporation of low molecular weight components of the crosslinking agent and tackifier and deterioration of adhesive properties tend to be prevented. The mixing time is preferably 5 to 90 minutes, more preferably 10 to 80 minutes, and even more preferably 20 to 70 minutes. By setting the mixing time to 5 minutes or more, each component tends to be uniformly dispersed. By setting the mixing time to 90 minutes or less, evaporation of low molecular weight components of the crosslinking agent and tackifier, deterioration of adhesive properties, and deterioration of the block copolymer tend to be prevented.

[0103] [Method of applying pressure-sensitive adhesive composition]

[0113] The method for applying the pressure-sensitive adhesive composition of the present embodiment is not particularly limited as long as the desired product can be obtained, and examples of the method include a method of dissolving the pressure-sensitive adhesive composition in a solvent and applying the solution, and a hot melt coating method of melting the pressure-sensitive adhesive composition and applying it. Among these, hot melt coating is preferred from the viewpoint of environmental pollution and ease of coating. Hot melt coating is broadly classified into contact coating and non-contact coating. "Contact coating" refers to a coating method in which a sprayer is brought into contact with a member or a film when applying a hot melt adhesive. "Non-contact coating" refers to a coating method in which a sprayer is not brought into contact with a member or a film when applying a hot melt adhesive. Contact coating methods are not particularly limited, but examples thereof include die coater coating, slot coater coating, and roll coater coating. Non-contact coating methods are not particularly limited, but examples thereof include spiral coating, which can be applied in a spiral shape, omega coating and control seam coating, which can be applied in a wavy shape, slot spray coating and curtain spray coating, which can be applied in a planar shape, dot coating, which can be applied in a dot shape, and bead coating, which can be applied in a line.

[0104] The adhesive composition of the present embodiment has a property that it has good thermal stability, is uniformly melted in a high-temperature tank at 100 to 200°C, and does not undergo phase separation. On the other hand, hot melt adhesives with poor thermal stability easily undergo phase separation of components in a high-temperature tank. Phase separation can cause clogging of tank filters and transport piping, so from this viewpoint, the adhesive composition of the present embodiment has excellent properties.

[0105] [Application] The adhesive composition of the present embodiment has a low viscosity, and therefore can be applied relatively easily at low temperatures, and has particularly excellent holding power. By utilizing such characteristics, the adhesive composition can be used for various adhesive tapes and labels, pressure-sensitive thin plates, pressure-sensitive sheets, surface protection sheets and films, backing adhesives for fixing various lightweight plastic molded products, backing adhesives for fixing carpets, backing adhesives for fixing tiles, adhesives, etc., and can be particularly suitably used as an adhesive for adhesive tapes. EXAMPLES

[0106] The present invention will be described in more detail below with reference to specific examples and comparative examples, but the present invention is not limited to the following examples and comparative examples. In the following Examples and Comparative Examples, the characteristics and physical properties of the polymers were measured by the following methods.

[0107] [(1): Characteristics of block copolymer composition] ((1-1) Content of vinyl aromatic compound monomer unit in block copolymer composition (hereinafter also referred to as styrene content), hydrogenation rate of vinyl bond in conjugated diene monomer unit before hydrogenation, and hydrogenation rate (H) of unsaturated double bond in conjugated diene monomer unit) The hydrogenation rate of the double bonds of the conjugated diene monomer units in the block copolymer composition was measured under the following conditions using a nuclear magnetic resonance (NMR) spectrometer. First, a large amount of methanol was added to the reaction solution after the hydrogenation reaction to precipitate and recover the block copolymer constituting the block copolymer composition. Next, the block copolymer was extracted with acetone, and the extract was vacuum dried. 1 The sample used for H-NMR measurement was 1 The conditions for H-NMR measurement are as follows. <Measurement conditions> Measuring equipment: JNM-LA400 (JEOL) Solvent: Deuterated chloroform Measurement sample: Samples taken before and after hydrogenation of the polymer Sample concentration: 50mg / mL Observation frequency: 400MHz Chemical shift reference: TMS (tetramethylsilane) Pulse Delay: 2.904 seconds Number of scans: 64 Pulse width: 45° Measurement temperature: 26℃

[0108] ((1-2) Weight average molecular weight) The weight average molecular weights of the components (a) and (b) constituting the block copolymer composition were determined based on the molecular weights of the peaks in the chromatograms using a calibration curve (created using the peak molecular weights of the standard polystyrene) determined from the measurement of commercially available standard polystyrene under the measurement conditions described below. First, a single peak having the lowest peak top molecular weight in the molecular weight range of 20,000 or more and having an area ratio of 0.1 or more relative to the total peak area of ​​the block copolymer composition, as calculated by peak division described below, was designated as component (a), and all peaks in the molecular weight range higher than that were designated as components (b). The weight average molecular weights of components (a) and (b) were determined by vertically dividing the GPC curves to the baseline at the inflection points between the peaks using the system software described below. Here, the inflection points between the peaks of components (a) and (b) were determined as the lowest vertical point (valley peak) between adjacent peaks. In addition, if the lowest points were consecutive, the midpoint was determined as the lowest point. Using the inflection points described above, vertical division was performed using the waveform separation function in the system software described above, and after division, each weight average molecular weight and area ratio was calculated. <Measurement conditions> GPC: ACQUITY APC system (manufactured by Nihon Waters Co., Ltd.) System (measurement and analysis) software: Empower3 Detector: RI Refractive index unit scale: 500μRIU Output full scale: 2000mV Sampling rate: 10 points / sec Column: ACQUITY APC XT125 (4.6mm x 150mm); 1 unit ACQUITY APC XT200(4.6mm×150mm);1 piece ACQUITY APC XT900(4.6mm×150mm);1 piece ACQUITY APC XT450(4.6mm×150mm);1 piece Solvent: THF Flow rate; 1.0mL / min Concentration: 0.1mg / mL Column temperature: 40°C Injection volume: 20μL

[0109] <(1-3) Weight average molecular weight of polymer block (A) contained in component (a)> The weight average molecular weight of the polymer block (A) contained in the component (a) was calculated from the weight average molecular weight of the component (a) and the content of the vinyl aromatic monomer unit (styrene).

[0110] <(1-4) Contents of component (a) and component (b) in block copolymer composition> The ratio of the area of ​​component (a) to the total peak area of ​​the elution curve measured in (1-2) above was defined as the content of component (a). The content of component (b) was determined as the ratio of the area of ​​all peaks in the molecular weight range higher than that of component (a) to the total peak area of ​​the elution curve measured in (1-2) above.

[0111] <(1-5): Contents and weight average molecular weights of components (b-1), (b-2), and (b-3)> In component (b), a peak having a peak top that is 1.5 to less than 2.5 times the weight average molecular weight of component (a) was designated component (b-1), a peak having a peak top that is 2.5 to less than 3.4 times the weight average molecular weight of component (a) was designated component (b-2), and a peak having a peak top that is 3.4 to less than 4.5 times the weight average molecular weight of component (a) was designated component (b-3). The ratio of the peak area of ​​each component to the total peak area of ​​the elution curve measured in (1-2) above was defined as the content of each component. The peak areas, weight average molecular weights, and weight average molecular weight ratios of components (b-1), (b-2), and (b-3) were determined by GPC measurement using the above-mentioned apparatus and conditions, followed by vertical division to the baseline at the inflection points between each peak on the GPC curve using the above-mentioned system software. Here, the inflection points between the peaks of components (b-1), (b-2), and (b-3) were taken as the lowest vertical point (valley peak) between adjacent peaks. If the lowest points were consecutive, the midpoint was taken as the midpoint. Using the inflection points, vertical division was performed using the waveform separation function in the above-mentioned system software, and after division, each weight average molecular weight, each weight average molecular weight ratio, and peak area were calculated.

[0112] <(1-6) Vinyl bond amount V of conjugated diene monomer unit before hydrogenation> The block copolymer composition before hydrogenation was used and the calculation was carried out by the Hampton method using an infrared spectrophotometer (FT / IR-230, manufactured by JASCO Corporation).

[0113] (2) Measurement of physical properties of adhesive composition (Preparation of adhesive composition) 100 parts by mass of the block copolymer composition of each of the Examples and Comparative Examples, 100 parts by mass of Quinton R100 (manufactured by Zeon Corporation) as a tackifier, 30 parts by mass of Process Oil NS-90S (manufactured by Idemitsu Kosan Co., Ltd.) as a softener, and 1 part by mass of 2-t-butyl-6-(3-t-butyl-2-hydroxy-5-methylbenzyl)-4-methylphenyl acrylate as a stabilizer were mixed and melt-kneaded at 180°C, 50 rpm, 30 minutes in a pressure kneader (model: DR0.5-3MB-E, Moriyama Corporation) to obtain a uniform hot melt pressure-sensitive adhesive composition.

[0114] <Melt Viscosity of Pressure-Sensitive Adhesive Composition> The melt viscosity of the adhesive composition was measured at temperatures of 160°C and 180°C using a Brookfield viscometer (DV-III manufactured by Brookfield Corporation).

[0115] (Preparation of adhesive tape) The molten adhesive composition was cooled to room temperature and dissolved in toluene to obtain a toluene solution. The obtained toluene solution was coated on a polyester film with an applicator, and then the film was left at room temperature for 30 minutes and in an oven at 70° C. for 7 minutes to completely evaporate the toluene, thereby preparing an adhesive tape. The coating thickness was 25 μm (substrate thickness: 38 μm).

[0116] <Adhesive properties of adhesive composition (1) (probe tack)> Using the pressure-sensitive adhesive compositions of Examples 1 to 9 and Comparative Examples 1 to 12, pressure-sensitive adhesive tapes measuring 30 mm in length and 30 mm in width were prepared as described above. The prepared adhesive tape was attached to the top surface of a 10 g load (cylindrical) of a probe tack tester (NTS-4800 / manufactured by Tester Sangyo Co., Ltd.) with the adhesive surface facing downward. A 5 mm diameter cylinder (made of stainless steel) was attached to the adhesive surface from below in a floating state for one second. Thereafter, the peeling force when the cylinder was peeled off was measured. The adhesion and peeling speed was 10 mm / sec.

[0117] <Adhesive properties of the adhesive composition (2) (adhesive strength)> Using the pressure-sensitive adhesive compositions of Examples 1 to 9 and Comparative Examples 1 to 12, pressure-sensitive adhesive tapes having a width of 25 mm were produced as described above. The prepared adhesive tape was attached to a SUS plate (SUS304), and the 180-degree peel force was measured at a peel speed of 300 mm / min.

[0118] <Adhesive properties of the adhesive composition (3) (holding power)> Using the pressure-sensitive adhesive compositions of Examples 1 to 9 and Comparative Examples 1 to 12, pressure-sensitive adhesive tapes having a width of 15 mm were produced as described above. The prepared adhesive tape was attached to a SUS plate (SUS304) with a contact area of ​​15 mm x 15 mm. Thereafter, a load of 1 kg was applied to the adhesive tape in the vertical direction at 50° C., and the time it was held until the adhesive tape slipped off was measured. The retention strength of each sample was judged based on the following criteria.

[0119] <Adhesive properties of adhesive composition (4) (balance between melt viscosity and adhesive performance)> The balance between melt viscosity and adhesive performance was judged based on the value obtained by dividing the retention time (min) obtained above by the measured melt viscosity (Pa·s) obtained above.

[0120] [Preparation of Block Copolymer Composition] (Preparation of hydrogenation catalyst) In the examples and comparative examples described later, the hydrogenation catalyst used in producing the block copolymer composition was prepared by the following method. A reaction vessel equipped with a stirrer was replaced with nitrogen, and 1 L of dried and purified cyclohexane was placed in the vessel. Next, 100 mmol of bis(η5-cyclopentadienyl)titanium dichloride was added, and while thoroughly stirring, an n-hexane solution containing 200 mmol of trimethylaluminum was added, and the mixture was allowed to react at room temperature for about 3 days. This gave a hydrogenation catalyst.

[0121] (Preparation of Block Copolymer Composition) <Example 1> Using a tank-type reactor equipped with a stirrer and a jacket and having an internal volume of 100 L, batch polymerization was carried out in the following manner. First, 36 L of cyclohexane was charged into the reactor and the temperature was adjusted to 55°C. After that, 0.143 parts by mass of n-butyllithium (hereinafter also referred to as "Bu-Li") was added per 100 parts by mass of the total amount of butadiene monomer and styrene monomer (hereinafter referred to as total monomers) charged into the reactor, and 0.28 moles of N,N,N',N'-tetramethylethylenediamine (hereinafter also referred to as "TMEDA") per mole of Bu-Li were added. Next, 24.0 parts by mass of styrene was added over 5 minutes, and the reaction was continued for another 15 minutes (the temperature reached 65° C. due to the polymerization reaction). At this point, the polymer solution was sampled and the polymerization conversion rate of styrene was measured, which was 100%. Next, a cyclohexane solution (concentration 40 parts by mass) containing 76.0 parts by mass of butadiene was continuously added to the reactor at a constant rate over 60 minutes, and then reacted for another 10 minutes. Three minutes after the reaction temperature reached a maximum temperature of 86°C, tetraethoxysilane was added as a coupling agent at 0.114 per 1 mole of Bu-Li, and a coupling reaction was carried out for 30 minutes. Then, 0.6 moles of methanol were added per 1 mole of Bu-Li to terminate the polymerization reaction, and a block copolymer composition was obtained. Next, the hydrogenation catalyst was added to the obtained block copolymer composition in an amount of 50 ppm in terms of titanium per 100 parts by mass of the copolymer, and a hydrogenation reaction was carried out at a hydrogen pressure of 0.9 MPa and a temperature of 90° C. for 45 minutes. Thereafter, 0.3 parts by mass of octadecyl-3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate was added as a stabilizer based on 100 parts by mass of the copolymer, to obtain a block copolymer composition 1.

[0122] <Example 2> Block copolymer composition 2 was obtained in the same manner as in Example 1, except that the amount of styrene was changed to 25 parts by mass and the amount of butadiene was changed to 75 parts by mass.

[0123] < Reference example 3> The same as Example 1 except that the amount of styrene was changed to 23 parts by mass and the amount of butadiene was changed to 77 parts by mass. In this manner, block copolymer composition 3 was obtained.

[0124] <Example 4> Block copolymer composition 4 was obtained in the same manner as in Example 1, except that the amount of Bu-Li was changed to 0.129 parts by mass relative to 100 parts by mass of the total monomers.

[0125] < Reference example 5> The amount of Bu-Li was changed to 0.185 parts by mass per 100 parts by mass of the total monomers. In the same manner as in Example 1, a block copolymer composition 5 was obtained.

[0126] < Reference example 6> The block copolymer composition was prepared in the same manner as in Example 1, except that the hydrogenation reaction time was changed to 60 minutes. Product 6 was obtained.

[0127] <Example 7> Block copolymer composition 7 was obtained in the same manner as in Example 1, except that the amount of TMEDA was changed to 0.05 mol per mol of Bu-Li and the hydrogenation reaction time was changed to 30 minutes.

[0128] <Example 8> Block copolymer composition 8 was obtained in the same manner as in Example 1, except that the amount of tetraethoxysilane was changed to 0.145 mol per 1 mol of Bu-Li and the amount of methanol was changed to 0.5 mol per 1 mol of Bu-Li.

[0129] <Example 9> Block copolymer composition 9 was obtained in the same manner as in Example 1, except that the amount of tetraethoxysilane was changed to 0.097 mol per 1 mol of Bu-Li and the amount of methanol was changed to 0.7 mol per 1 mol of Bu-Li.

[0130] <Comparative Example 1> Block copolymer composition 10 was obtained in the same manner as in Example 1, except that the amount of Bu-Li was changed to 0.112 parts by mass per 100 parts by mass of total monomers, the amount of styrene was changed to 22 parts by mass, the amount of butadiene was changed to 78 parts by mass, and tetraethoxysilane was changed to 0.126 mol per 1 mol of Bu-Li.

[0131] <Comparative Example 2> Block copolymer composition 11 was obtained in the same manner as in Example 1, except that the amount of Bu-Li was 0.112 parts by mass relative to 100 parts by mass of total monomers, the amount of styrene was 26 parts by mass, the amount of butadiene was 74 parts by mass, the amount of tetraethoxysilane was 0.138 mol per 1 mol of Bu-Li, and the coupling reaction time was 15 minutes.

[0132] <Comparative Example 3> Block copolymer composition 12 was obtained in the same manner as in Example 1, except that the amount of TMEDA was 0.2 mol per mol of Bu-Li, the amount of styrene was 25 parts by mass, the amount of butadiene was 75 parts by mass, the amount of tetraethoxysilane was 0.152 mol per mol of Bu-Li, and the maximum temperature during the butadiene reaction was changed to 75°C by cooling the reactor.

[0133] <Comparative Example 4> Block copolymer composition 13 was obtained in the same manner as in Example 1, except that the amount of Bu-Li was changed to 0.138 parts by mass, the amount of styrene was changed to 28 parts by mass, and the amount of butadiene was changed to 72 parts by mass, relative to 100 parts by mass of all monomers.

[0134] <Comparative Example 5> Block copolymer composition 14 was obtained in the same manner as in Example 1, except that the amount of Bu-Li was changed to 0.150 parts by mass, the amount of styrene was changed to 17 parts by mass, and the amount of butadiene was changed to 83 parts by mass, relative to 100 parts by mass of all monomers.

[0135] <Comparative Example 6> Block copolymer composition 15 was obtained in the same manner as in Example 1, except that the amount of Bu-Li was changed to 0.109 parts by mass relative to 100 parts by mass of all monomers.

[0136] <Comparative Example 7> Block copolymer composition 16 was obtained in the same manner as in Example 1, except that the amount of Bu-Li was changed to 0.226 parts by mass relative to 100 parts by mass of all monomers.

[0137] <Comparative Example 8> Block copolymer composition 17 was obtained in the same manner as in Example 1, except that the hydrogenation reaction time was changed to 90 minutes.

[0138] <Comparative Example 9> Block copolymer composition 18 was obtained in the same manner as in Example 1, except that the hydrogenation reaction time was changed to 30 minutes.

[0139] <Comparative Example 10> A block copolymer composition 19 was obtained in the same manner as in Example 1, except that the amount of tetraethoxysilane was changed to 0.059 mol per 1 mol of Bu-Li and the amount of methanol was changed to 0.8 mol per 1 mol of Bu-Li.

[0140] <Comparative Example 11> A block copolymer composition 20 was obtained in the same manner as in Example 1, except that the amount of tetraethoxysilane was changed to 0.178 mol per 1 mol of Bu-Li and the amount of methanol was changed to 0.4 mol per 1 mol of Bu-Li.

[0141] <Comparative Example 12> Block copolymer composition 21 was obtained in the same manner as in Example 1, except that the amount of Bu-Li was changed to 0.109 parts by mass per 100 parts by mass of total monomers, the coupling agent was changed to ethyl benzoate, and the amount of coupling agent added was changed to 0.193 mol per 1 mol of Bu-Li.

[0142] Tables 1 and 2 show the physical property values ​​obtained for each of Examples 1 to 9 and Comparative Examples 1 to 12. The properties of each of Examples 1 to 9 and Comparative Examples 1 to 12 obtained as described above were evaluated by the above-mentioned methods. Furthermore, adhesive tapes were obtained by the above-mentioned method for producing an adhesive tape, and the obtained adhesive tapes were evaluated by the above-mentioned methods. The evaluation results are shown in Tables 1 and 2.

[0143] In the above evaluation, the balance between the melt viscosity and the adhesive performance was calculated by dividing the retention time by the melt viscosity at 180°C, and those with this value of 2.0 or more were judged to be block copolymer compositions and adhesive compositions having an excellent balance between low viscosity and holding power performance.

[0144] [Table 1]

[0145] [Table 2] [Industrial Applicability]

[0146] INDUSTRIAL APPLICABILITY The block copolymer composition and pressure-sensitive adhesive composition of the present invention have industrial applicability as materials for solution-type and hot-melt-type adhesives and pressure-sensitive adhesives.

Claims

1. Component (a) is 50% by mass or more and 70% by mass or less, A block copolymer composition containing 30% by mass or more and 50% by mass or less of component (b), the component (a) is a block copolymer containing a polymer block (A) mainly made of one vinyl aromatic monomer unit and a polymer block (B) mainly made of at least one conjugated diene monomer unit, and having a weight average molecular weight of 50,000 or more and 80,000 or less; the component (b) is a block copolymer containing at least two polymer blocks (A) mainly composed of vinyl aromatic monomer units and at least one polymer block (B) mainly composed of conjugated diene monomer units, the component (b) is a polymer obtained by coupling the component (a) with a tetrafunctional or higher coupling agent, The component (b) includes a component (b-1) having a weight average molecular weight ratio of 1.5 or more to less than 2.5 relative to the weight average molecular weight of the component (a), a component (b-2) having a weight average molecular weight ratio of 2.5 or more to less than 3.4 relative to the weight average molecular weight of the component (a), and a component (b-3) having a weight average molecular weight ratio of 3.4 or more to less than 4.5 relative to the weight average molecular weight of the component (a), The content of the component (b-3) is 35% by mass or more based on the total amount of the component (b), The content of vinyl aromatic monomer units in the component (a) and the component (b) is 22.0 mass% or more and 26.0 mass% or less with respect to the total amount of the component (a) and the component (b), the vinyl bond content V (%) of the conjugated diene monomer units contained in the component (a) and the component (b) before hydrogenation is 25% or more; a hydrogenation rate H (%) of the unsaturated double bonds of the conjugated diene monomer units contained in the component (a) and the component (b) is 30% or more and 55% or less, and the hydrogenation rate H (%) satisfies the following formula (1') in relation to the vinyl bond content V (%), the hydrogenation rate of vinyl bonds of the conjugated diene monomer units contained in the component (a) and the component (b) before hydrogenation is 80% or more; Block copolymer compositions. V+25>H>V+15...Formula (1')

2. The weight average molecular weight of the polymer block (A) contained in the component (a) is 14,000 or more and 19,000 or less. The block copolymer composition of claim 1 .

3. said component (a) being a block copolymer represented by (A-B) and / or (A-B)X; The component (b-1) is (A-B) 2 X, The component (b-2) is (A-B) 3 X, The component (b-3) is (A-B) 4 X, and X are block copolymers, respectively represented by The block copolymer composition according to claim 1 or 2. (A represents polymer block (A), B represents polymer block (B), and X represents a residue of a coupling agent or a residue of a polymerization initiator.)

4. 100 parts by mass of the block copolymer composition according to any one of claims 1 to 3; 1 to 250 parts by mass of a tackifier; 0 to 120 parts by weight of a softener; A pressure-sensitive adhesive composition comprising:

Citation Information

Patent Citations

  • JP1969017037Y1

  • Measuring device for ammonia nitrogen present in water

    JP1981049958A

  • Adhesive composition

    JP2017190428A

  • Block copolymer composition and adhesive composition

    WO2015111669A1

  • Block copolymer and adhesive composition

    WO2015111675A1